Dados geocronológicos para o soco pré-Mesozoico localizado a Oeste da Falha Porto-Tomar: implicações geodinâmicas - Santos, Telmo M. Bento Dos (2023)
SUMMARY: Geochronological data from the pre-Mesozoic basement of the Lusitanian Basement (West of the Porto-Tomar Fault) was obtained. Results show a predominant Cadomian/Pan-African and Eburnean inheritance/source, placing this sector as a peri-Gondwanan domain. However, two major differences can be seen in the data: samples with a clear absence in Mesoproterozoic ages vs. samples with a clear presence of these ages and Silurian-Devonian ages. If the former show clear signs of affinity with the Ossa-Morena Zone, the latter are similar to the South Portuguese Zone, being one of the samples, probably deposited in the Middle-Upper Devonian, interpreted as having a mixed source.